Dopaminergic system involvement in the memory: Modulating effects of glucose. - Abrams, Darren G. (University of Ottawa (Canada), 1999)
We examined whether the dopaminergic system plays a role in the ability of glucose to improve memory. Specifically, we were interested in determining if glucose could reverse a memory-impairment produced by a dopaminergic D 2/D3 receptor antagonist. The first three experiments used an operant training paradigm to test memory. Experiment 1 established the most effective memory-improving dose of glucose in our specific memory task. Experiment 2 was designed to establish which dose of eticlopride, a dopaminergic D2/D3 antagonist, was most effective at impairing memory in our specific task. Experiment 3 examined the effect of an injection of a 3 g/kg dose of glucose on the memory-impairing effect of a 0.1 mg/kg dose of eticlopride. Finally, Experiment 4 examined the effect of an injection of LY-171555, a dopaminergic D2 agonist, on circulating blood glucose levels. The results of Experiment 1 demonstrated that a 3 and 4 g/kg dose of glucose significantly improved memory. Experiment 2 revealed that a 0.1 mg/kg dose of eticlopride significantly impaired memory. Experiment 3 demonstrated that glucose could not reverse the memory-impairment produced by eticlopride and Experiment 4 showed that LY-171555 did not result in an increase in circulating blood glucose.
Keywords: Biology, Neuroscience.